Family Violence and Depression in Wives of Alcoholics and Nonalcoholics: Examining the Impact of Alcoholism on Family Violence and Depression in Married Women (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The purpose of the present investigation was to study the family violence and depression in wives of alcoholics and non alcoholics. For this purpose family violence was measured with the help of family violence scale constructed by Rai and depression was measured with the help of Beck Depression Inventory constructed by back. The sample consisted of 100 wives of alcoholics and non alcoholics. A one factor design was used. There was one independent variable. The independent variable was alcohol varied at two levels i.e. alcoholics and non alcoholics. Mean, SD, and t-value were calculated. On the base of obtained result it was found that there is significant difference in family violence and depression of wives of alcoholics and non alcoholics.